Konsepsi pengajaran pensyarah dan kaitannya dengan pendekatan pembelajaran pelajar - Sihes, Ahmad Johari (2009)
The general purpose of this descriptive research is to determine lecturers’ teaching conceptions and the factors influencing their teaching conceptions. The research also studied the relations between lecturers’ teaching conceptions and students’ approaches to learning. The teaching conceptions examined are Knowledge Transmission (KT) Orientation and Learning Facilitation (LF) Orientation. The factors being studied were lecturers’ background consisting of teaching experience, academic discipline and position while the teaching environment factor consists of class size, academic workload, support for teaching, control of teaching and students’ characteristics. Stratified random sampling was used to determine the sample and a total of 313 lecturers were involved to study the lecturers’ teaching conceptions. Data were collected from the lecturers using Lecturers’ Conceptions of Teaching and Learning (LCTL) questionnaire to determine the lecturers’ teaching conceptions meanwhile Perception of Teaching Environment (PTE) questionnaire was used to evaluate perception of their teaching environment. A total of 34 lecturers and 779 students were involved in the study to determine the relations between lecturers’ teaching conceptions and students’ approaches to learning. Data from students were collected using Revised Two-Factor Study Process Questionnaire (R-SPQ-2F). Descriptive, correlations, multiple correlations, three-way ANOVA, one-way ANOVA, one-way MANOVA and multiple regression statistics were used to analyse the data set at 0.05 significance level. Results revealed that lecturers are more inclined towards the LF Orientation (mean=4.40) compared to the KT Orientation (mean=4.21). There was no significant difference in the KT Orientation among the lecturers based on their background factor. However lecturers from different academic background have significantly different levels of LF Orientation. The lecturers’ perception of their teaching environment was at medium level (mean=3.48) and has significant relationships with both teaching conceptions orientations (KT; R=0.230, p=0.005) (LF; R=0.363, p=0.0001). Support for teaching element significantly contributed 4.2% towards the variance in the KT Orientation while position, control of teaching and support for teaching elements significantly contributed 12.8% towards the variance in the LF Orientation. Research findings also showed that there was a significant difference in change of surface learning approach among students taught by lecturers who are high in LF Orientation and low in LF Orientation. A model to enhance lecturers’ teaching conceptions that reduce students’ surface learning approach in university is proposed.